Cesarean scar pregnancy: clinicians challenge - Vora, Priyanka Harshavardhan; Bansal, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A case of caesarean scar ectopic pregnancy managed diagnosed early on transvaginal ultrasound and managed successfully by sequential approach of methotrexate and hysteroscopic removal preserving the woman’s fertility is discussed below. Ectopic pregnancy i.e. implantation of the blastocyst outside the endometrium of the uterine cavity occurs in 1.9% of reported pregnancies.